Implementasi Fuzzy Tsukamoto Dalam Menentukan Upah Gaji Karyawan Perbulan - Siti Maysaroh Saragih; Ayu Lestari; Mahadir Soleh Hutasuhut (Brahmana : Jurnal Penerapan Kecerdasan Buatan, 2020)
In a company, salary is a salary for employees who have been working for a month. However, in order to provide fair salary to all employees, the company must determine the criteria for providing salary. By using fuzzy logic, wages can be determined by going through the following stages: Fuzzification, Formation of the knowledge base, Fuzzy Inference, and Defuzzification. One of the fuzzy logic methods that can be used is the Tsukamoto method, where this method has an output in the form of firm values. To determine the salary, the data is collected from the Central Statistics Agency website in accordance with the criteria to be examined. With this research, employers can use the calculations from this research to determine salary salaries for their employees quickly, well, and precisely. So that the problem of determining the wages of their employees' salaries can be resolved properly.